HUBUNGAN DUKUNGAN SUAMI DALAM PERSALINAN DENGAN NYERI PERSALINAN DI RUANG KENANGA RSUP DR RIVAI ABDULLAH PALEMBANG TAHUN 2022 - Lisda Maria; Indah Oktalia (Jurnal Kesehatan dan Pembangunan, 2023)
Labor is a physiological thing for women but labor pain can cause stress and labor will be longer. Husband's support becomes an important role in overcoming mother's pain because husband is the closest person to mother. This study aims to determine the relationship between husband's support in labor and labor pain in the Kenanga Room, RSUP dr. Rivai Abdullah Palembang in 2022. This research method is quantitative observational analytic with a cross-sectional approach. The population in this study were all married couples who were in the first stage of labor in the Kenanga Room, RSUP dr. Rivai Abdullah Palembang in 2022 as many as 52 people with a total sample of 34 people. Data analysis using the chi square test. The results showed that most of the husbands supported the mother at the time of delivery (55.9%), while the rest were less supportive (44.1%), most of the mothers in labor had moderate labor pain (52.9%), then mild labor pain (26, 5%) and the rest was severe labor pain (20.6%). There is a relationship between husband's support in labor and labor pain in the Kenanga Room, RSUP dr. Rivai Abdullah Palembang in 2022 (p value 0.032). The conclusion in this study is that husband's support is sufficient to reduce labor pain in maternity mothers. Therefore, researchers suggest to husbands so that at the time of delivery they can mentally prepare to provide assistance to the mother. Keywords: Husband's Support, Labor Pain,The First Stage of Active Phase